Diagnosa Penyakit Malaria Menggunakan Metode Case Base Reasoning (CBR) (Studi Kasus: RSUD Djoelham Kota Binjai) - Abdullah Husein; Rusmin Saragih; Husnul Khair (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2024)
The application of information technology has been widely used in medicine. This application provides convenience and smoothness in the medical world to detect symptoms of various diseases, especially malaria. Malaria is still included in the endemic diseases suffered by the community in Binjai City, the more malaria patients, of course the more doctors are needed/work to diagnose patients. Artificial intelligence is one solution and helps doctors in supporting decision making for certain diseases. Building a system to diagnose malaria using the Case-Based Reasoning (CBR) method offers various significant advantages. CBR utilizes experience and knowledge from previous cases, allowing the system to provide a more accurate diagnosis based on patterns and symptoms that have occurred in the past.